Cardiac fibrosis as a determinant of ventricular tachyarrhythmias. Issue 6 (6th March 2014) - Morita, Norishige; Mandel, William J.; Kobayashi, Yoshinori; Karagueuzian, Hrayr S.
Abstract: Animal and emerging clinical studies have demonstrated that increased ventricular fibrosis in a setting of reduced repolarization reserve promotes early afterdepolarizations (EADs) and triggered activity that can initiate ventricular tachycardia and ventricular fibrillation (VT/VF). Increased ventricular fibrosis plays a key facilitatory role in allowing oxidative and metabolic stress‐induced EADs to manifest as triggered activity causing VT/VF. The lack of such an arrhythmogenic effect by the same stressors in normal non‐fibrotic hearts highlights the importance of fibrosis in the initiation of VT/VF. These findings suggest that antifibrotic therapy combined with therapy designed to increase ventricular repolarization reserve may act synergistically to reduce the risk of sudden cardiac death.